Agricultural and empowerment pathways from land ownership to women's nutrition in India. Issue 4 (20th March 2020) - Harris‐Fry, Helen; Krishnan, Sneha; Beaumont, Emma; Prost, Audrey; Gouda, Sanghamitra; Mohanty, Satyanarayan; Pradhan, Ronali; Rath, Suchitra; Rath, Shibanand; Pradhan, Shibnath; Mishra, Naba Kishore; Allen, Elizabeth; et al.
Abstract: Land size is an important equity concern for the design of 'nutrition‐sensitive' agricultural interventions. We unpack some of the pathways between land and nutrition using a cross‐sectional baseline survey data set of 4, 480 women from 148 clusters from the 'Upscaling Participatory Action and Videos for Agriculture and Nutrition' trial in Keonjhar district in Odisha, India. Variables used are household ln‐land size owned (exposure) and maternal dietary diversity score out of 10 food groups and body mass index (BMI; kg/m 2 ) (outcomes); and mediators investigated are production diversity score, value of agricultural production, and indicators for women's empowerment (decision‐making in agriculture, group participation, work‐free time and land ownership). We assessed mediation using a non‐parametric potential outcomes framework method. Land size positively affects maternal dietary diversity scores [ β 0.047; 95% confidence interval (CI) (0.011, 0.082)] but not BMI. Production diversity, but not value of production, accounts for 17.6% of total effect mediated. We observe suppression of the effect of land size on BMI, with no evidence of a direct effect for either of the agricultural mediators but indirect effects of β −0.031 [95% CI (−0.048, −0.017)] through production diversity and β −0.047 [95% CI (−0.075, −0.021)] through value of production. An increase in land size positively affects women's decision‐making, which in turn negatively affects maternal BMI. The positive effect of work‐free time on maternal BMI is suppressed by the negative effect of household land size on work‐free time. Agriculture interventions must consider land quality, women's decision‐making and implications for women's workload in their design.